2016
DOI: 10.1080/14740338.2017.1259310
|View full text |Cite
|
Sign up to set email alerts
|

Safety of proteasome inhibitors for treatment of multiple myeloma

Abstract: Proteasome inhibitors (PIs) have revolutionized the treatment of multiple myeloma and are a backbone of therapy. Bortezomib, the first PI approved, has shown efficacy in both front-line and relapsed/refractory settings however the development of resistance and side effects such as peripheral neuropathy can limit its use. The second generation PIs carfilzomib and ixazomib, both approved in relapsed/refractory cases, may help to overcome resistance mechanisms and increase tolerability. While bortezomib is approv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
53
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(55 citation statements)
references
References 63 publications
0
53
0
2
Order By: Relevance
“…Bmib is mainly used as a therapeutic agent for refractory multiple myeloma in hematology clinic, due to its potent anti-tumor activity and yet-unknown biological function (16). It has been reported that Bmib caused the high incidence of neutropenia and stomatitis (17), peripheral neuropathy (18) and epidermal necrolysis (19). We also found potent cytotoxicity of Bmib against OSCC cell lines as well as normal oral cells, especially oral keratinocytes.…”
Section: Discussionmentioning
confidence: 51%
“…Bmib is mainly used as a therapeutic agent for refractory multiple myeloma in hematology clinic, due to its potent anti-tumor activity and yet-unknown biological function (16). It has been reported that Bmib caused the high incidence of neutropenia and stomatitis (17), peripheral neuropathy (18) and epidermal necrolysis (19). We also found potent cytotoxicity of Bmib against OSCC cell lines as well as normal oral cells, especially oral keratinocytes.…”
Section: Discussionmentioning
confidence: 51%
“…In recent years, with the successful application of proteasome inhibitor bortezomib in the treatment of multiple myeloma, ubiquitination of proteins has entered a new research level. 16 A series of anti-tumor drugs targeting ubiquitination-related enzymes, including E1, E2, E3 and DUBs, have been developed for cancer treatment. 17 For example, PYR-41, an inhibitor of E1, was used in anticancer research.…”
Section: Discussionmentioning
confidence: 99%
“…Difficult symptoms such as PN can result in significant disability and pain (Colson, ). It is crucial that there is frequent assessment of neuropathic symptoms and the early detection of neuropathic pain before it gets progressively worse (Colson, ; Schlafer, Shah, Panjic, & Lonial, ).…”
Section: Discussionmentioning
confidence: 99%